2014
DOI: 10.7577/formakademisk.802
|View full text |Cite
|
Sign up to set email alerts
|

Systems Thinking in Design: Service Design and self-Services

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…During the development path of Service Design, it can be seen that Service Design already introduced some systemic perspective (e.g., Darzentas & Darzentas, 2014;Manzini et al, 2001;Sangiorgi & Pacenti, 2010;van der Bijl-Brouwer, 2017;Yulia & Roberta, 2018) and emphasized its role in the service systems transformation (e.g., Koskela-Huotari et al, 2021;Patrício et al, 2020;Villari, 2022). However, it is essential to recognize that with the rapid development of the world, Service Design is facing increasingly significant complexity and large-scale problems brought about by the dynamic changes inside and outside the service systems, multi-actor dynamic interaction, and interdependence challenges in its environment (Dorst, 2015;Manzini, 2011;Villari, 2022;Vink, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…During the development path of Service Design, it can be seen that Service Design already introduced some systemic perspective (e.g., Darzentas & Darzentas, 2014;Manzini et al, 2001;Sangiorgi & Pacenti, 2010;van der Bijl-Brouwer, 2017;Yulia & Roberta, 2018) and emphasized its role in the service systems transformation (e.g., Koskela-Huotari et al, 2021;Patrício et al, 2020;Villari, 2022). However, it is essential to recognize that with the rapid development of the world, Service Design is facing increasingly significant complexity and large-scale problems brought about by the dynamic changes inside and outside the service systems, multi-actor dynamic interaction, and interdependence challenges in its environment (Dorst, 2015;Manzini, 2011;Villari, 2022;Vink, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…-Systems thinking perspective derived approaches to the design of services Systems thinking as a thinking tool for dealing with complexity has been integrated into many other fields and disciplines as early as the twentieth century, such as biology, information theory, management, engineering, and cybernetics (Darzentas & Darzentas, 2014). With the development of systems thinking, there was a growing acknowledgment and emphasis on the contribution of soft systems thinking (Checkland, 1981) in dealing with the high complexity of ill-structured problems (Checkland, 2000), as compared to hard systems thinking, which contributes to deal with structured systems problems (Checkland, 1981).…”
Section: Towards a Systemic Perspective Of Service Designmentioning
confidence: 99%
“…In a complex and dynamic environment, such as manufacturing support services, there are many managers who tend to design several parts of the system separately to provide an overall service solution (Seddon 2008). This will develop a service system where managers need to manage the parts in order to control the whole (Darzentas and Darzentas 2014). Ackoff (1981) found that reductionist approach of managing system parts without understanding the interaction between them is a main cause for system failure.…”
Section: Systems Thinking Designmentioning
confidence: 99%
“…For this type of work, team members are empowered and trusted to make decisions on the work they have in hands. They also enjoy open channels of communication with their peers and with other teams and departments where necessary to share knowledge and information (Darzentas and Darzentas 2014). It is due to this virtue that team members become self-directed by reflecting on the system operations they have, and then learning how to make their own rules and decisions to absorb work environment changes (Dunnion and O'Donovan 2014).…”
Section: Systems Thinking Designmentioning
confidence: 99%
“…The integration of these three factors require the designer to have the ability to be, at the same time, analytical and emphatic, rational and emotional, methodical and intuitive, oriented by plans and constraints, but spontaneous (Darzentas and Darzentas, 2014). This type of reasoning is also mentioned as “abductive thinking.” This is often different from rational deductive and inductive reasoning (Robbins and Devitt, 2017).…”
Section: Introductionmentioning
confidence: 99%